The Role of Transforming Growth Factor-β Signaling in Myxomatous Mitral Valve Degeneration - Tang, Qiyu; McNair, Andrew J.; Phadwal, Kanchan; Macrae, Vicky E.; Corcoran, Brendan M. (Frontiers in Cardiovascular Medicine, 2022)
Mitral valve prolapse (MVP) due to myxomatous degeneration is one of the most important chronic degenerative cardiovascular diseases in people and dogs. It is a common cause of heart failure leading to significant morbidity and mortality in both species. Human MVP is usually classified into primary or non-syndromic, including Barlow’s Disease (BD), fibro-elastic deficiency (FED) and secondary or syndromic forms (typically familial), such as Marfan syndrome (MFS), Ehlers-Danlos syndrome and Filamin-A mutation. Despite different etiologies the diseased valves share pathological features consistent with myxomatous degeneration. To reflect this common pathology the condition is often called myxomatous mitral valve degeneration (disease) (MMVD) and this term is universally used to describe the analogous condition in the dog. MMVD in both species is characterized by leaflet thickening and deformity, disorganized extracellular matrix, increased transformation of the quiescent valve interstitial cell (qVICs) to an activated state (aVICs), also known as activated myofibroblasts. Significant alterations in these cellular activities contribute to the initiation and progression of MMVD due to the increased expression of transforming growth factor-β (TGF-β) superfamily cytokines and the dysregulation of the TGF-β signaling pathways. Further understanding the molecular mechanisms of MMVD is needed to identify pharmacological manipulation strategies of the signaling pathway that might regulate VIC differentiation and so control the disease onset and development. This review briefly summarizes current understanding of the histopathology, cellular activities, molecular mechanisms and pathogenesis of MMVD in dogs and humans, and in more detail reviews the evidence for the role of TGFβ.